2017
DOI: 10.1002/bip.23016
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic structure of pectin in solution

Abstract: Mesoscopic structure of pectin with different molecular characteristics was investigated by means of small angle X-ray scattering (SAXS), electrokinetic measurements and data modelling. The influence of a broad range of pH (2-7) on chain conformation in the dilute and semi-diluted regime was investigated. Scattering data and concomitant analysis revealed two length scales at all environmental conditions studied. pH showed greater influence at acidic values (pH 2.0) enhancing the globular component of the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…It has been shown that RG-I segments impart greater flexibility to the pectin chains [ 23 ]. In particular, persistence length that can used as a measure of chain flexibility has been found to be lower for okra pectin chains with greater content in RG-I regions [ 24 ]. Consequently, the additional flexibility of the chains creates shorter separation distances between droplets resulting in ineffective steric stabilization compared to those with lower amounts of RG-I (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that RG-I segments impart greater flexibility to the pectin chains [ 23 ]. In particular, persistence length that can used as a measure of chain flexibility has been found to be lower for okra pectin chains with greater content in RG-I regions [ 24 ]. Consequently, the additional flexibility of the chains creates shorter separation distances between droplets resulting in ineffective steric stabilization compared to those with lower amounts of RG-I (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The low pH decreases the biopolymer charge due to the protonation of the carboxyl groups of the GalA residues and therefore aggregation is more intensive at very low pH values due to the neutralization of the chains (Gilsenan et al., 2000). It has been demonstrated for pectin extracted from okra that at a low pH, the chain has a compact conformation whereas high pH values result in an extended conformation (Alba, Bingham, & Kontogiorgos, 2017; Alba, Kasapis, & Kontogiorgos, 2015a). For the main pectin sources, that is citrus, apple, and sugar beet, the pectin conformation is semiflexible (Axelos & Thibault, 1991; Cros et al., 1996; Garnier, Axelos, & Thibault, 1993; Morris, Ralet, Bonnin, Thibault, & Harding, 2010), that is the persistence length is of the order of 10 to 17 monomers (Dumitriu, 2004).…”
Section: The Secondary Structure Of Pectin Chainsmentioning
confidence: 99%
“…For the main pectin sources, that is citrus, apple, and sugar beet, the pectin conformation is semiflexible (Axelos & Thibault, 1991; Cros et al., 1996; Garnier, Axelos, & Thibault, 1993; Morris, Ralet, Bonnin, Thibault, & Harding, 2010), that is the persistence length is of the order of 10 to 17 monomers (Dumitriu, 2004). The neutral sugars on the side of the RGI backbone are not influenced by pH and serve as the basis for compact conformations over the entire range of pH (Alba et al., 2017; Morris et al., 2008). Therefore, the coil‐type conformation depends on the degree of branching by neutral sugars.…”
Section: The Secondary Structure Of Pectin Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). The uronic acid components of the polysaccharides found in mucilages from the Malvaceae have a negative charge at neutral pH, which can cause intra-molecular repulsion resulting in an extended conformation [46,47]. This favours inter-molecular interactions between the chains rather than self-association.…”
Section: Rheological Measurementsmentioning
confidence: 99%